PERILAKU DAN LOYALITAS KONSUMEN MADU DI KOTA BENGKULU - Selmi, Selmi; Asriani, Putri Suci; Saepuddin, Rustama (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2017)
Indonesia with a current population of nearly 240 million people, is the 4th largest population in the world need quite a lot of honey. The research objective was to analyze customer characteristics honey based group of consumers, identify the attributes of honey products that affect on purchase decisions, analyze consumer behavior and customer loyalty to honey, analyze the marketing mix right is based on the analysis of consumer behavior and consumer perception of the local honey product, and formulate strategies marketing of honey in the city of Bengkulu. Determining the location of the research conducted on honey outlets in the city of Bengkulu, the selection was conducted intentionally (purposive).The location of this study were at 8 stores/outlets of honey and herbs as well as a fairly large supermarket, honey outlets which was set as the study site. Data collection was done during the months of June-August 2015. The number of respondents in this study was 96. The data collected in this research were primary and secondary data that being collected to obtain the study aims to analysis of consumer behavior is processed using Importance Performance Analysis (IPA), and analysis of loyalty consumer using the Customer Satisfaction Index (CSI). The method results Importance Performance Analysisis based on Cartesian diagram shows that there is one attribute that is considered important and is the main priority in determining customer satisfaction. The attribute was the special price for every purchase at a time/day/month special like, Ramadhan, Eid and other interest consumen calculation. Based Satisfaction Index, the level of consumer satisfaction reached 71.30% honey. The calculation results show that in general consumers of honey was categorized satisfied (0.61 <CSI ? 0.80).